Role of Liver Enzymes and Blood Parameters in Relation to Histopathological Severity in Benign and Malignant Liver Lesions - Abdul Ahad Mehboob, Adnan-Ur-Rehman, Sham Lal Prithiani, Fatima Rashid, Rehan Akhtar, Aliya Zaman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Liver lesions comprise a broad spectrum of pathological conditions ranging from benign tumors to aggressive malignancies. Histopathological examination remains the definitive diagnostic tool; however, non-invasive laboratory markers that reflect histopathological severity are increasingly important for early risk stratification and clinical decision-making. Objective: To assess the relationship between liver enzymes and selected blood parameters in relation to histopathological severity in patients with benign and malignant liver lesions. Methods: This cross-sectional analytical study was conducted at Medical Teaching Institution Hayatabad Medical Complex, Peshawar, and Liaquat Institute of Medical & Health Sciences, Thatta, Pakistan, from June 2022 to May 2023. A total of 100 patients with histopathologically confirmed liver lesions were included. Liver function tests, including alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, gamma-glutamyl transferase, and total bilirubin, along with hematological parameters such as hemoglobin, platelet count, international normalized ratio, and serum albumin, were recorded. Lesions were classified as benign or malignant, and malignant lesions were graded histopathologically. Statistical analysis was performed to determine associations between laboratory parameters and histopathological severity. Results: Malignant liver lesions demonstrated significantly higher liver enzyme levels and bilirubin concentrations compared to benign lesions. Hemoglobin and platelet counts were significantly reduced, while international normalized ratio values were prolonged in malignant cases. Increasing histopathological grade was associated with progressive elevation of liver enzymes and worsening hematological and coagulation parameters. Conclusion: Liver enzymes and blood parameters show significant correlation with histopathological severity in liver lesions. These routinely available laboratory markers may serve as useful, non-invasive tools for assessing disease severity and supporting clinical management. Keywords: Liver lesions; Liver enzymes; Histopathology; Hematological parameters; Hepatic malignancy; Disease severity.